Effects of the IFRS introduction: perspective from an early stadium to the time after the mandatory adoption - Nicolas Schrödl; Christian Klein (Universität Hohenheim, Institut für Betriebswirtschaftslehre, 2009)
Regulators' expectations to the IFRS introduction are high. In our analyses we measure by different variables for market liquidity how inter alia reporting quality and investors' preference developed with IFRS adopter and non IFRS adopter firms over the years, starting in the time of the early adoption. The results from around 35,000 firm year observations in eleven countries show that only particular adopter firms generally show higher liquidity values over the years. Overall we can observe a clear trend. Market liquidity values are significantly higher for IFRS adopter firms during the years before 2005, the year in which reporting of consolidated accounts according to IFRS became mandatory for basically all publicly traded companies within the European Union and several other countries. Predominantly these values decrease over the years and turn into an advance for non IFRS adopter firms in the years after the mandatory adoption. Concluding, the results are supportive for the investors' long term preference, after distorting influences during the adoption years, for the non IFRS adopter firms.
urn:nbn:de:bsz:100-opus-3526
Keywords: 650